The effect of seasonal changes in mineral nutrition and secondary metabolism of Epipactis palustris (Orchidaceae) on the rhizosphere soil ecosystem - N. V. Zaimenko; N. S. Chernikova; N. P. Didyk; N. A. Pavliuchenko; O. P. Yunosheva; I. P. Kharytonova; O. V. Zakrasov; A. M. Gnatiuk; M. B. Gароnenko (Regulatory Mechanisms in Biosystems, 2026)
Epipactis palustris (L.) Crantz is a rare orchid species whose ecological and biochemical strategies of adaptation remain insufficiently studied, despite its relevance for biodiversity conservation and ecosystem stability. This research aimed to investigate the seasonal changes in mineral nutrition, secondary metabolism, enzymatic activity, allelopathic potential, and microbial composition of the rhizosphere soil. Fieldwork was conducted in 2024 at the M. M. G ryshko National Botanical Garden of the National Academy of Sciences of Ukraine (Куiv). The study revealed that E. palustris demonstrates pronounced physiological and biochemical flexibility during the growing season, maintaining mineral balance even under conditions of reduced soil macro- and microelement availability. Elevated accumulation of Ca, Mg, Sr, and Si in the leaves indicated selective ion uptake and the development of ion-homeostatic mechanisms, which are crucial for structural stability and seasonal adaptation. Stable levels of brassinosteroids in the plants throughout the season reflected its ability to sustain hormonal–mineral regulation of growth, photosynthetic activity, and antioxidant defense. In summer, decreased laccase activity and humus content, combined with increased bicarbonate concentration and soil electrical conductivity, pointed to intensified transformation of organic matter and mobilization of mineral elements, creating favorable conditions for plant nutrition. The rhizosphere soil exhibited moderate allelopathic activity, supporting symbiotic interactions with microbial communities. Seasonal shifts in microbial complexes suggested dynamic pathways of organic matter turnover, while the consistent presence of nitrogen-fixing microorganisms ensured nitrogen supply. Taken together, these findings highlight the integrated role of mineral nutrition, hormonal regulation, and rhizosphere interactions in maintaining functional stability of E. palustris . The study provides new insights into the mechanisms of adaptation of rare orchids to environmental stress and emphasizes their connection with mycorrhizal associations. Beyond its ecological significance, this work contributes to the development of scientific approaches for in situ and ex situ conservation of rare orchid species, offering a framework for sustainable management of vulnerable plant populations under changing environmental cond i tions.